2015
DOI: 10.1107/s139900471501384x
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for amino-acid recognition and transmembrane signalling by tandem Per–Arnt–Sim (tandem PAS) chemoreceptor sensory domains

Abstract: Chemotaxis, mediated by methyl-accepting chemotaxis protein (MCP) receptors, plays an important role in the ecology of bacterial populations. This paper presents the first crystallographic analysis of the structure and ligand-induced conformational changes of the periplasmic tandem Per-Arnt-Sim (PAS) sensing domain (PTPSD) of a characterized MCP chemoreceptor. Analysis of the complex of the Campylobacter jejuni Tlp3 PTPSD with isoleucine (a chemoattractant) revealed that the PTPSD is a dimer in the crystal. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 48 publications
(45 reference statements)
7
84
0
Order By: Relevance
“…We succeeded in producing folded protein and high-quality crystals by following the refolding procedure that we have recently developed (25,26). The purified protein was monomeric in solution, in line with previous studies that showed PTPSDs from other receptors to be also monomeric in solution (16,20,(25)(26)(27). X-ray crystallographic analysis of CtaB PTPSD in complex with various amino acid ligands is expected to provide an explanation of the structural basis behind the broad ligand specificity of this receptor.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…We succeeded in producing folded protein and high-quality crystals by following the refolding procedure that we have recently developed (25,26). The purified protein was monomeric in solution, in line with previous studies that showed PTPSDs from other receptors to be also monomeric in solution (16,20,(25)(26)(27). X-ray crystallographic analysis of CtaB PTPSD in complex with various amino acid ligands is expected to provide an explanation of the structural basis behind the broad ligand specificity of this receptor.…”
Section: Resultssupporting
confidence: 64%
“…We have previously observed that expression of periplasmic sensory domains of bacterial MCP receptors in E. coli often results in their deposition predominantly in inclusion bodies (16,20,(25)(26)(27). The recombinant ligand sensing domain of P. fluorescens CtaB is another example of a molecule of this type that required extraction from IBs and refolding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tlp3 recognizes its ligand isoleucine directly, via its membrane-distal PAS domain (22). The structural analysis of Tlp3 and structure-guided sequence alignments revealed that receptors for amino acids, that have a tandem-PAS sensing domain that recognizes the ligand directly, contain a conserved consensus motif DXXX(R/K)CWYXXA (22). We note that CtaA peri contains this motif and is therefore likely to bind at least some of its amino acid ligands directly.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported the crystal structure of the periplasmic sensing domain of C. jejuni transducer-like protein 3 (Tlp3) harboring two PAS domains. Tlp3 recognizes its ligand isoleucine directly, via its membrane-distal PAS domain (22). The structural analysis of Tlp3 and structure-guided sequence alignments revealed that receptors for amino acids, that have a tandem-PAS sensing domain that recognizes the ligand directly, contain a conserved consensus motif DXXX(R/K)CWYXXA (22).…”
Section: Introductionmentioning
confidence: 99%